A encruzilhada entre deficiência e emprego: os caminhos do direito do trabalho pela perspectiva deficiente - Maria Clara Persilva Soares (2021)
This thesis deals with the place occupied by workers with disabilities in Brazil, from an analysis of how the Labor Law is inserted in the context of the production of disability. Therefore, the study was divided into four moments. Initially, we sought to explain and problematize concepts and terminologies that are necessary for the understanding and progress of this research, and then, we look at historical aspects, in order to situate disability as a social phenomenon, historically constructed based on the fictitious notion of normality. Based on this understanding, an attempt was made to analyze the development of Labor Law from a disabled perspective. Afterwards, we turned our gaze to the Brazilian reality and the country's legal system, recounting the evolution of labor in order to include workers with disabilities. Subsequently, in order to diagnose the place occupied by these workers today and its relationship with current Law, quantitative and qualitative data relating to people with disabilities were examined, from the drafting of the Law about quotas in 1991 to the present time. At the end of the research, it was concluded that the Labor Law is crossed by the foundations that produce disability, reproducing and legitimizing ableism, at the same time that it has an essential role in promoting social inclusion.